Solid‐State Conversion Reaction to Enhance Charge Transfer in Electrochromic Materials. Issue 6 (2nd March 2015) - Lin, Feng; Nordlund, Dennis; Weng, Tsu‐Chien; Moore, Rob G.; Gillaspie, Dane T.; Jones, Kim M.; Dillon, Anne C.; Richards, Ryan M.; Engtrakul, Chaiwat
<x xml:space="preserve">Abstract</x> Interface engineering has attracted great interest and is essential for the fabrication of thin‐film devices, such as smart windows. In this study, a solid‐state conversion reaction for the development of an interlayer enriched with lithium peroxide (Li2O2) is presented for an electrochromic device. We demonstrate that efficient lithium insertion and electron transport can be achieved by the inclusion of a Li2O2‐rich interlayer between an active electrochromic material and Li ion solid‐state electrolyte layer. The presence of a Li2O2‐rich interlayer enhances electrochromic efficiency, kinetics, optical contrast, and bleached‐state transparency in a nickel oxide‐based electrochromic thin film. This work opens up new opportunities to enhance the functionalities of thin‐film devices by solid‐state conversion reactions.